General Education and Museum Education: Between Singularity and Plurality - Antonella Nuzzaci (Universidad Complutense de Madrid, 2006)
The article examines the relationship between general and museum education, and between the various discipline and museum educations. The term "education" is quite frequent in the daily use and -as we know- in its broader meaning it suggest the teaching activity, but in a more specific meaning it refers to the knowledge pertaining to this activity. This identifies an area of research and knowledge within educational sciences defined as general education. In reality there are many forms it could take (e.g. special education addressed to disabled subjects, comparative education examining the teaching methods used throughout different school systems etc.) as well as many different forms of museum education. The article studies also the problem of recognition and specificity of the museum education contribution in comparison with other fields, even if the structure of the specialized museum educations (art, archaeological, historical museums, etc.) make some general education abstracts emerging.